Pengaruh Media Games Baamboozle Terhadap Minat Belajar Siswa Materi Bangun Datar Kelas V SD Negeri 205 Palembang - Vio Arinda Rahmania; A. Heryanto; Sunedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research is motivated by the problem that the author has identified, which is the lack of interest in learning among fifth-grade students at SD Negeri 205 Palembang, such as students not focusing on learning, students being less diligent in doing assignments given by the teacher, lack of motivation, taking a long time to do questions and students not being active in asking questions. This study aims to determine the effect of baamboozle games-based learning media on students' interest in learning flat shapes of grade V SD Negeri 205 Palembang. The research method used is the quasi-experimental design method with a nonequivalent control group design. This research was conducted at SD Negeri 205 Palembang with a population of grade V SD totaling 97 with a research sample of 46 students through a sampling technique in this study, namely saturated samples. Data collection techniques in the form of observation, questionnaires and documentation. Data analysis techniques with normality tests, homogeneity tests and hypothesis tests. The results of the study showed that the average results of the posttest scores of the control and experimental classes, namely the control class was 81.0 and the experimental class was 89.5, where the results of the pretest questionnaires of the control class and the experimental class were 57.3 and 60.5 respectively. The results of the hypothesis test obtained a t-count value of 5.073> t-table value of 2.015 or a significance value of t-count 0.001 <significant t-table 0.05, then Ho was rejected and Ha was accepted, meaning that there was a significant influence of baamboozle games-based learning media on students' interest in learning flat shapes in class V of SD Negeri 205 Palembang. It can be concluded that bamboozle games learning media can increase students' interest in learning, because this media is a fun media.